Effects of a single session of transcranial direct current stimulation on upper limb movements in children with cerebral palsy: A randomized, sham-controlled study. (18th August 2017) - Moura, Renata Calhes Franco; Santos, Cibele; Collange Grecco, Luanda; Albertini, Giorgio; Cimolin, Veronica; Galli, Manuela; Oliveira, Claudia
ABSTRACT: Introduction : Motor impairment in children with spastic hemiparetic cerebral palsy (CP) is generally more prominent in the affected upper limb, leading to limitations in hand function stemming from deficiencies in motor coordination and selective motor control as well as muscle weakness, slower execution of movements and deficient integration of sensory-motor information. Objective : Determine the effect of a single session of anodal transcranial direct current stimulation (tDCS) combined with functional training on the spatiotemporal variables of upper arm movements in children with spastic hemiparesis. Method : A randomized, sham-controlled trial with a blinded evaluator was conducted involving 20 children with CP between 6 and 12 years of age. The spatiotemporal variables of the upper limbs were analyzed by comparing the results of Evaluation 1 (before stimulation) and Evaluation 2 (immediately after stimulation). The protocol consisted of a 20-minute session of functional training of the paretic upper limb combined with tDCS administered over the primary motor cortex of the hemisphere contralateral to the motor impairment at an intensity of 1 mA. The participants were randomly allocated to two groups: experimental group (anodal tDCS) and control group (sham tDCS). Results : Statistically significant ( p < 0.05) reductions in total movement duration and returning movement duration were found in both the paretic and non-paretic limbs in the group submitted to active tDCS. No significant differences were found in the control group for any of the variables analyzed. Conclusion : A single session of anodal tDCS over the primary motor cortex of the hemisphere ipsilateral to the brain lesion led to momentary motor improvements in both upper limbs of the children with spastic hemiparetic CP analyzed in the present study.